QUICK RESPONSE CODE (QR CODE)-ASSISTED INTERACTIVE MEDIA ON PTERYDOPHYTA FOR HIGH SCHOOL STUDENT - Mawaddah, Kuni (Jurnal Pendidikan Biologi, 2017)
In accordance with the demands of the 21st century and the Curriculum 2013, learners are required to face the challenges of the future, namely the demands of globalization and advancement of information technology. One of the technological discoveries is the Quick Response Code (QR Code). Utilization of QR Code in the field of education can as a means of presenting information by connecting various media. The purpose of this study is to develop interactive media teaching materials Pteridophyta Division berbantaun QR Code. The existence of interactive media teaching materials is expected students are able to interact with media realia so as able to describe the characteristics of Divisio in the world of plants and its role for survival on earth. The research method used is model development of 4D model adapted from Thiagarajan. In this research we only do research until design stage because of fund and time limitation. Data analysis can not be done because of this interactive media not yet implemented. After the implementation of interactive media can be done descriptive quantitative analysis. The result of the research is interactive media powerpoint macro product of QR Code-assisted Pteridophyta Division with basic competence in SMA X class that is 3.9 describes divisio characteristics in plant world and its role for survival on earth.